Exploring the impact of the COVID-19 pandemic on doctors’ core workplace needs: a qualitative study of internal medicine trainees in Scotland - Victoria Ruth Tallentire; Ailsa Lauren Hamilton; Joanne Kerins; Jemma Pringle; Fiona Farquhar (BMJ Open)
Objectives This study aimed to explore how the COVID-19 pandemic has impacted the workplace core needs of internal medicine (IM) trainees in Scotland.Design This qualitative study used an observational approach of interprofessional workshops combined with subsequent individual interviews with IM trainees. Workshops and interviews were audiorecorded, transcribed verbatim and analysed utilising NVivo software. Template analysis was used with the Autonomy/control, Belonging and Competence (ABC) of doctors’ core needs outlined in the 2019 General Medical Council report Caring for doctors, caring for patients as a conceptual lens for the study.Setting The national IM boot camp in Scotland includes a 2-hour interprofessional workshop which is trainee led and explores current challenges in the workplace, including the impact of the pandemic on such relationships.Participants Twelve workshops, involving 72 trainees, were included with ten trainees taking part in the subsequent interview process. Trainees representing all four regions in Scotland were involved.Results Trainees described all core needs having been impacted by the pandemic. They described a loss of autonomy with emergency rotas but also through a pervasive sense of uncertainty. The data revealed that work conditions improved initially with additional resources which have since been removed in some areas, affecting trainees’ sense of value. Analysis found that belonging was affected positively in terms of increased camaraderie but also challenged through inability to socialise. There were concerns regarding developing competence due to a lack of teaching opportunities.Conclusions Using the ABC of doctor’s core needs as a conceptual framework for this study highlighted the impact of the COVID-19 pandemic on all domains for IM trainees in Scotland. It has highlighted an opportunity to foster the renewed sense of camaraderie among healthcare teams, while rebuilding work conditions to support autonomy and competence.